Requirements for The Success of Electronic Banking Services and Their Role in Achieving Competitive Advantage (A field study on private Syrian Commercial banks) - قاسم , سامر; السكري, أحمد; ماء البارد, باسل (Latakia University Journal - Economic and Legal Sciences Series, 2022)
This study aimed to assess the availability of electronic banking services requirements in private Syrian Commercial banks, as they are superior to public banks in providing these services to customers, and the role of their availability in achieving a competitive advantage for these banks that makes customers prefer them over public banks. To achieve this, two main hypotheses were formulated, and the researcher used the questionnaire method to collect the data that was analyzed using statistical tests, the most important of which are: the One-Sample T. test, the Pearson Correlation test, and the simple regression analysis. The researcher reached several results, the most important of which are: The requirements for the success of electronic banking services in the banks under study are good, and the banks under study achieve a good competitive advantage with regard to the dimensions of excellence, the lowest cost, the right time, innovation and basic competencies, and there is a good direct relationship between the availability of requirements for the success of electronic banking services and achieving the competitive advantage in the banks in question studying.